Monograph on the Cillaeinae (Coleoptera: Nitidulidae) from the Australian Region with comments on the taxonomy of the subfamily - Kirejtshuk, Alexander G.; Kovalev, Alexey V. (Zootaxa, 2022)
General review of the taxonomy and composition of the subfamily Cillaeinae with description of Conotelini trib. nov. (type genus: Conotelus Erichson, 1843 with some necessary notes on the position and rank of some recent and fossil taxa are given. The rank of the following supraspecific taxa are changed: former subgenus Paracillaeopsis Kirejtshuk, 2001 is now regarded as a separate genus (stat. nov.) and former genus Grouvellepeplus Kirejtshuk, 2001 is considered to be a subgenus (stat. nov.) of the genus Liparopeplus Murray, 1864. There is completed a revision of all cillaeine genera and species found in Australia and some others from adjacent territories, including the genera Adocimus Murray, 1864 with new subgenus Belonotus subgen. nov. (type species: Adocimus (Belonotus) bartenevi sp. nov.), Allenipeplus Kirejtshuk et Kovalev 2016, Brachypeplus Erichson, 1842, Brittonoma Kirejtshuk et Kovalev, 2016, Caledomus Kirejtshuk et Kovalev, 2017, Cillaeopeplus, Ithyphenes Murray, 1864, Laferollaeus gen. nov. (type species: Laferollaeus angustissimus sp. nov.), Matthewsianus gen. nov. (type species: Brachypeplus olliffi Blackburn, 1902), Onicotis Murray, 1864 and Oniphenes gen. nov. (type species: Oniphenes lobanovi sp. nov.). The following new species are described: Adocimus (Belonotus) bartenevi sp. nov., Brachypeplus instriatus sp. nov. B. makarovi sp. nov., B. nypicola sp. nov., Cillaeopeplus rectinotus sp. nov., C. temporalibus sp. nov., Ithyphenes australiaensis sp. nov., I. marinae sp. nov., I. rectifrons sp. nov., Matthewsianus polinae sp. nov., Oniphenes bicoloratus sp. nov., O, lobanovi sp. nov. and O. subunicolor sp. nov. The systematic placement is re-defined for the following species: Adocimus (Belonotus) modiglianii (Grouvelle, 1897), comb. nov. (former Cillaeus Laporte, 1835), A. (B.) nitidulus (Grouvelle, 1897), comb. nov. (former Brachypeplus), Brachypeplus cascus Powell et Cline, 2021, comb. nov. (former Palaeopeplus Powell et Cline, 2021), Brittonoma mandibulare (Kirejtshuk, 2011), comb. nov. and B. pygidiatum (Kirejtshuk, 2011), comb. nov. (former Brittonema Kirejtshuk, 2011), Campsopyga xanthura (Murray, 1864), comb. nov. (former Hypodetus Murray, 1864), Cillaeopeplus rastrus (Gillogly, 1962), comb. nov. (former Cillaeus), Ithyphenes angustus (Grouvelle, 1917), comb. nov. (former Platynema Ritsema, 1885), I. breviceps (Murray, 1864), comb. nov. (former Orthogramma Murray, 1864), I. dentipes (Murray, 1864), comb. nov. (former Orthogramma), I. fissiceps (Murray, 1864), comb. nov. (former Orthogramma), I. fuscipennis (Murray, 1864), comb. nov. (former Orthogramma), I. japonicus (Hisamatsu, 1985), comb. nov. (former Platynema), I. longiceps (Murray, 1864), comb. nov. (former Orthogramma), I. olliffi (Ritsema, 1885), comb. nov. (former Platynema), I. planiceps (Murray, 1864), comb. nov. (former Orthogramma), I. puncticeps (Murray, 1864), comb. nov. (former Orthogramma), I. ritsemai (Grouvelle, 1897), comb. nov. (former Orthogramma), I. saundersii (Murray, 1864), comb. nov. (former Orthogramma) and Matthewsianus olliffi (Blackburn, 1902), comb. nov., (former Brachypeplus). The following generic and species names are considered to be junior synonyms (senior synonym listed first): Brachypeplus Erichson, 1842 = Palaeopeplus Powell et Cline, 2021, syn. nov.; Ithyphenes Murray, 1864 = Platynema Ritsema, 1885, syn. nov.; Adocimus bellus Murray, 1864 = A. nigripennis Reitter, 1880, syn. nov. and A. dimidiatus Reitter, 1877, syn. nov.; Nitidulopsis aequalis Walker, 1858 = Brachypeplus (Selis) pallidus Dasgupta et Pal, 2019, syn. nov. and B. (S.) riang Dasgupta, Pal et Hodge, 2015, syn. nov.; Brachypeplus (Brachypeplus) obesus Grouvelle, 1895 = B. (B.) arengae Kirejtshuk, 1994, syn. nov. and very probably B. (B.) registernus Dasgupta et Pal, 2019; Brachypeplus (Selis) apicalis Murray, 1864 = B. (S.) fimbriatus Reitter, 1880, syn. nov.; B. (S.) dorsalis Grouvelle, 1897 = B. (S.) decoratus Grouvelle, 1917, syn. nov. and very probably B. (S.) ornatus Grouvelle, 1914; Brachypeplus (Tasmus) basalis: Murray, 1864 = B. (T.) brevicornis Sharp, 1878, syn. nov.; Brachypeplus (Tasmus) binotatus Murray, 1864 = B. cowleyi Blackburn, 1902, syn. nov. = B. koebelei Blackburn, 1902 and B. murrayi Macleay, 1873, syn. nov.; Brachypeplus kemblensis Blackburn, 1902 = Brachypeplus mauli Gardner et Clasey, 1962, syn. nov.; Brachypeplus (Brachypeplus) macLeayi Murray, 1864 = B. inquilinus Lea 1912, syn. nov.; Brachypeplus olliffi Blackburn, 1902 = B. insignis Lea, 1925, syn. nov. Because of insufficiency of available material the synonymy of Brachypeplus (Brachypeplus) nitidulus Grouvelle, 1897 and Cillaeus modiglianii Grouvelle, 1897 (currently both in Adocimus (Belanotus subgen. nov.)) is considered preliminary. The recent studies of additional specimens make it possible to consider Brachypeplus apicalis Murray, 1864 and B. dorsalis Grouvelle, 1897 (previously synonymized by Kirejtshuk, 2005) as separate species. The lectotypes of the following species are designated: Adocimus nigripennis Reitter, 1880, Brachypeplus barronensis Blackburn, 1902, B. basalis Erichson, 1842, B. Cowleyi Blackburn, 1902, B. inquilinus Lea, 1912, B. insignis Lea, 1925, B. kemblensis Blackburn, 1902, B. Koebelei Blackburn, 1902, B. Murrayi Macleay, 1873, B. Olliffi Blackburn, 1902, B. planus Erichson, 1842, B. wattsensis Blackburn, 1902, B. xanthorrhoeae Lea, 1925, Brachypeplus (Brachypeplus) nitidulus Grouvelle, 1897, B. (B.) obesus Grouvelle, 1895, B. (Selis) apicalis Murray, 1864, B. (S.) caudalis Murray, 1864, B. (S.) dorsalis Grouvelle, 1897, B. (S.) fimbriatus Reitter, 1880, B. (Tasmus) binotatus Murray, 1864, B. (T.) blandus Murray, 1864, B. (T.) brevicornis Sharp, 1878, Cillaeus Modiglianii Grouvelle, 1897, Ithyphenes Bouchardi Grouvelle, 1907, I. Gestroi Reitter, 1880, Brachypeplus (Onicotis) auritus Murray, 1864, Orthogramma breviceps Murray, 1864, O. dentipes Murray, 1864. O. fuscipennis Murray, 1864 and Platynema Olliffi Ritsema, 1885 are designated. The composition of the genus Ithyphenes and synonymy of the names proposed for it (Orthogramma Murray, 1864, nec R.L., 1817 et Guenée, 1852 and Platynema) are discussed and substantiated. The erroneous identification of Brachypeplus macleayi invasive pest of bees in U.S.A. is corrected (Sagili et al. 2016 published these data with the wrong name “Brachypeplus basalis”). The mature larvae of Brachypeplus aff. instriatus sp. nov. and Onicotis auritus are described. The key to genera of the cillaeine genera from Australia and adjacent territories, and also keys to Australian and Tasmanian species of the genera Brachypeplus, Ithyphenes and Oniphenes gen. nov. are presented.